Caste matters in public policy : issues and perspectives - Choragudi, Rahul; Pellissery, Sony, 1972-; Jayaram, N., 1950- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Caste in India, despite its historical resilience, has been undergoing transformation since independence. If caste as a system of rigid stratification has been on the decline, castes as autonomous interest-serving groups have been on ascendance. This book critically engages with the changing notions of caste and its intersection with public policy in India. It discusses key issues such as social security, internal reservation, the idea of Most Backward Classes, caste issues among non-Hindu religious communities, caste in census, caste in market, and service castes and urban planning. Drawing on in-depth case studies from states including Andhra Pradesh, Delhi, Karnataka, Punjab, Tamil Nadu, Telangana, and West Bengal, the volume explores the cyclical process of how caste drives policies, and how policies in turn shape the reality of caste in India. It looks at the impact of factors like protective discrimination, adult franchise and democratic decentralization, horizontal and vertical mobilisation, land reforms, and religious conversion on social mobility, and traditional hierarchy in India. Empirically rich and analytically rigorous, this book will be an excellent reference for scholars and researchers of public policy, public administration, sociology, exclusion studies, social work, law, history, economics, political science, development studies, social anthropology, and political sociology. It will also be of interest to public policy and development practitioners"--
Introduction: The career of caste in public policy / Rahul Choragudi, Sony Pellissery, and N. Jayaram -- Caste in and out of place : state, market, and culture / Stig Toft Madsen -- Enumerating caste in the census : is it useful for public policy? / N. Jayaram -- Awareness and access to social security among the unorganised worker households : a study of scheduled caste sub-plan and tribal sub-plan in Karnataka / D. Rajasekhar and R. Manjula -- Addressing graded inequality among the scheduled castes : internal reservation as a strategy / Arvind Narrain and Basawa Prasad Kunale -- Caste and politics : reservation policy in Tamil Nadu / Saravana Raja -- Economic opportunity, protective discrimination, and the changing jati relations : an ethnographic study in a coastal village in Andhra Pradesh / Rahul Choragudi -- Caste and public policy : the case of West Bengal / Antara Ray -- Accommodating service-caste group needs within urban policies for development : a study of dhobis in Delhi / Subhadra Mitra Channa -- Despite equality : Sikhs and the caste issue / Paramjit S. Judge -- Caste and caste discrimination among Christians and Muslims : a case for revisiting the ambit of protective discrimination policy / Gaurang Sahay -- Epilogue: Caste in public policy analysis - rediscovering public sphere through institutionalist lens / Sony Pellissery.
Includes bibliographical references and index.
Keywords: Caste -- Government policy -- India; Caste -- Political aspects -- India; India -- Politics and government -- 1947-; India -- Social conditions -- 1947-